2010
DOI: 10.1177/1049732310387935
|View full text |Cite
|
Sign up to set email alerts
|

Silent Endurance and Profound Loneliness: Socioemotional Suffering in African Americans Living With HIV in the Rural South

Abstract: We explored how community responses to HIV contribute to distress in African Americans living with HIV in the rural South of the United States. We listened to the voices of community members through focus groups and African Americans with HIV through interviews. Community avoidance of HIV, negative views of HIV, and discriminatory behavior powerfully affected the distress of people living with HIV (PLWH). Ongoing distress, coupled with limited support, led to a life in which many PLWH endured their pain in sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Descriptions of the influences of poverty included inadequate housing, homelessness, and inability to buy basic necessities such as food, medicine, and transportation. Seven of the nine articles reported that at least half of the study participants were surviving on an annual income less than $10,000 (Gaskins et al, 2011;Kempf et al, 2010;KonkleParker et al, 2008;Mallory, 2008;Miles et al, 2011;Phillips et al, 2011;Vyavaharkar et al, 2008). Lack of education was mentioned in three of the articles Phillips et al, 2011;Vyavaharkar et al, 2008).…”
Section: Economic Stability and Educationmentioning
confidence: 91%
See 4 more Smart Citations
“…Descriptions of the influences of poverty included inadequate housing, homelessness, and inability to buy basic necessities such as food, medicine, and transportation. Seven of the nine articles reported that at least half of the study participants were surviving on an annual income less than $10,000 (Gaskins et al, 2011;Kempf et al, 2010;KonkleParker et al, 2008;Mallory, 2008;Miles et al, 2011;Phillips et al, 2011;Vyavaharkar et al, 2008). Lack of education was mentioned in three of the articles Phillips et al, 2011;Vyavaharkar et al, 2008).…”
Section: Economic Stability and Educationmentioning
confidence: 91%
“…Unemployment and lack of skilled jobs in rural areas were mentioned in five articles Miles et al, 2011;Moneyham et al, 2010;Phillips et al, 2011;Vyavaharkar et al, 2008). Participants talked about unemployment as, ''I don't have no income or anything'' and ''No jobs'' (Phillips et al, 2011).…”
Section: Economic Stability and Educationmentioning
confidence: 96%
See 3 more Smart Citations